The association between circulating 25-hydroxyvitamin D metabolites and type 2 diabetes in European populations: a meta-analysis and Mendelian randomisation analysis - Zheng, J-S; Luan, J; Sofianopoulou, E; Sharp, SJ; Day, FR; Imamura, F; Gundersen, TE; Lotta, LA; Sluijs, I; Stewart, ID; Shah, RL; van der Schouw, YT; et al. (Public Library of Science, 2020)
Background Prior research suggested a differential association of 25-hydroxyvitamin D (25(OH)D) metabolites with type 2 diabetes (T2D), with total 25(OH)D and 25(OH)D3 inversely associated with T2D, but the epimeric form (C3-epi-25(OH)D3) positively associated with T2D. Whether or not these observational associations are causal remains uncertain. We aimed to examine the potential causality of these associations using Mendelian randomisation (MR) analysis.